Radiographic characteristics of bone metastases from hepatocellular carcinoma - Chen, Hai-yan; Ma, Xiu-mei; Bai, Yong-rui (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Different carcinomas have different characteristics, which may play a crucial role in diagnosis and treatment. Our study was aimed at understanding the development pattern of bone metastasis from hepatocellular carcinoma, based on its imaging characteristics, so as to provide a more targeted treatment. Material and methods : Forty two patients (123 lesions) with hepatocellular carcinoma hospitalized from June 2006 to June 2011 underwent radiotherapy for bone metastasis in our department. Clinical and imaging data were analyzed retrospectively (based on CT imaging, also with reference to MRI, ECT, or PET-CT, etc.). Results: One hundred of 123 lesions were vertebral metastases; 23 were non-vertebral. The major form of bone destruction was osteolytic change. Metastasis in the vertebral body was found in 87.8%, and lesions were well distributed in various sections. Vertebral appendix metastasis accounted for 52%, where lesions could be independent of vertebral body metastasis. Formation of a soft tissue mass in bone metastasis was found in 68.6% of all patients. The center of the mass from a vertebral body metastasis was mostly located at the site of the lesion; masses from the vertebral appendix and the pelvis, on the other hand, often presented as a “peripheral mass”. Masses were not formed in lesions with pure osteoblastic changes. Conclusions : The most common radiographic feature is an osteolytic lesion, either replaced by soft tissue mass, or invaded by soft tissue mass from the vicinity, which often cause compression syndrome. Vertebral appendix metastasis can exist independently from vertebral body metastasis, which should be paid more attention to avoid missed diagnosis.